The professional profile of quality teacher - Rosanna Tammaro; Marika Calenda; Concetta Ferrantino; Maura Guglielmini (Firenze University Press, 2016)
The paper examines in depth the importance of teachers, seen as professionals able to generate an improvement on the quality and effectiveness of instruction and education. The teacher profile describes a complex profession, which does not perform only in the classroom but also in the whole school and in the community, in a permanent development. The overview on Italian and European models profile expected for teachers sheds light the gradual emerging of new competences in relation to current challenges of education. The expertise of teachers is seen as a set of cognitive, affective, social and instrumental competences, in which assume particular importance the specific characteristics of the educational context. Il profilo professionale dell'insegnante di qualità Nel contributo si pone al centro l'importanza della figura dell'insegnante, intesa come professionalità capace di generare un miglioramento rispetto alla qualità e all'efficacia di istruzione e formazione. Il profilo dell'insegnante descrive una professione complessa, che non si esplica solo in classe, ma anche nella scuola e nella comunità, in uno sviluppo permanente. L'excursus sui modelli italiani ed europei dei profili attesi per gli insegnanti mette in luce il progressivo emergere di competenze nuove in relazione alle sfide attuali dell'educazione. L'expertise degli insegnanti è intesa come un insieme di competenze cognitive, affettive, sociali e strumentali, in cui particolare rilevanza è assunta dal carattere situato, dunque alle specificità del contesto educativo.